Novel Modulation of Isolated Bidirectional DC-DC Converter for Energy Storage Systems - Dung, Nguyen Anh; Chiu, Huang-Jen; Lin, Jing-Yuan; Hsieh, Yao-Ching; Chen, Hui-Ting; Zeng, Bo-Xiang (IEEE transactions on power electronics, 2019)
In this study, a novel modulation of an isolated three-phase bidirectional dc-dc converter is proposed for the high-voltage input power supply to low-voltage output energy storage systems. The wye-delta connection of the transformers is employed to reduce the voltage stress at the high side and the current stress at the low side of the transformers. Frequency control allows the output voltage regulation, and a phase-shift algorithm with a resonant tank is proposed following with the switching frequency to reduce the frequency range with the specific power. Furthermore, the zero-voltage-switching condition for all mosfet s in the entire power range, which is the major restriction of a single-phase converter, is also discussed in this paper. The three-phase wye-delta converter significantly reduces the ripple of inductor current compared with that of a single-phase converter. A 2 kW prototype converter was built and successfully tested to verify the capability of such control modulation.